Maternal vitamin D deficiency induces transcriptomic changes in newborn rat lungs. Issue 199 (May 2020) - Mandell, Erica; Ryan, Sharon; Seedorf, Gregory J.; Gonzalez, Tania; Abman, Steven H.; Fleet, James C.
Highlights: Maternal vitamin D deficiency disrupts lung development in offspring. The lung transcript profile of pups from vitamin D deficient dams is disrupted. Pathways for lung development are disrupted. Pathways for inflammation and innate immunity are stimulated. Abstract: Vitamin D deficiency (VDD) during pregnancy is common and related to several maternal and fetal morbidities. Vitamin D (VD) plays a role in normal lung development and VDD causes abnormal airway, alveolar, and vascular growth in newborn rats. Here we use an unbiased transcriptomic approach to identify pathways altered in the lungs of offspring from VDD dams. The lungs of newborn offspring from VD replete and VDD dams were removed and RNA from these samples were analyzed using Affymetrix microarrays. Data were RMA normalized, differential gene expression was determined using Significance Analysis of Microarrays (5 % FDR) and pathway enrichment analysis was assessed. There were 2233 differentially expressed transcripts between the VDD and control lungs (1889 up, 344 down). Consistent with the suppression of lung growth in the VDD group, there were significant suppression of signal transduction pathways related to vascular biology and anabolic signaling pathways, e.g. the insulin-like growth factor-1 receptor (IGF-1R), fibroblast growth factor (FGF), cell cycle control. A major, enriched functional category was upregulation of pathways related to the innate immune system, including pathways for granulocyte and macrophage development, chemotaxis, and activation of cytokine signaling through Jak/Stat (e.g. resulting in higher IL1 α and β ). We conclude that VDD during fetal development alters multiple pathways beyond the predicted angiogeneic alterations. These changes either contribute to, or reflect, the abnormal airway, alveolar, and vascular growth seen in the neonatal lung resulting from maternal VDD. The pattern also suggests abnormal lung development caused by maternal VDD creates a proinflammatory milieu that could contribute to the suppression of lung growth and development.